Correlates of stress among female adolescents - Fam, Jia Yuin *; Siti, Nor Yaacob (Malaysian Psychological Association, UKM, 2018)
Excessive stress during adolescence might contribute to various problems. Given that female adolescents tend to perceive more stress than male adolescents, the present study aimed to determine the relationships between parent-adolescent relationship, prosocial behaviour, academic self-efficacy, and stress among female adolescents in Malacca, Malaysia. Participants of the present study are 235 female school-going adolescents aged between 13 and 19 years old. Results of Pearson correlation analysis revealed that parent-adolescent relationship, prosocial behaviour, and academic self-efficacy were negatively correlated with stress. Additionally, all the three independent variables significantly predicted stress among female adolescents, where parent-adolescent relationship was the strongest predictor of stress. In essence, female adolescents who reported more positive relationship with parent, higher prosocial behaviour, and higher academic self-efficacy tend to have lower stress. The current findings highlight the significant role of parents and individual factors in combating stress among female adolescents. Parents should maintain affectionate relationship with their female adolescent-aged children. Related authorities as well as parents can help promote prosocial behaviour and academic selfefficacy among adolescents